Food problem of the eastern region of Ukraine caused by the war - Kazakova, Nadiia; Neustroieva, Gelena; Hromov, Vadym (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article deals with the scientifically substantiated analyses of the food problem of the eastern region of Ukraine based on its essential importance for the world problem of avoiding hunger. Taking into account the fact that the potential of external production exceeds the needs of the domestic market it is necessary to conduct a research of solving food problems when planning the development of the agricultural sector of the Ukrainian economy.. This article considers such analytical issues estimating that Ukraine has been among the top five exporters of grain and legume resources for many years. Ukraine is one of the main countries that contributes to the agricultural sector of the world economy. The activities of future specialists, when dealing with the food problem, depend on the content and nature of the knowledge that not only the coronavirus pandemic, but also armed conflicts in most of the specified countries and climate change, several years of drought contributed to problems with agricultural production in the region. The general provisions on analysis of various options for solving this problem are given and it is estimated that the analytical approach is the most optimal, since it allows you to build a diagram for comparing percentage of the most popular agricultural crops in the sown areas. It is advisable to consider the process of selecting most of the data that have been collected before the invasion. This research paper reveals the fact that much of the concern is related to shortages in the supply of staple crops such as wheat, corn and oilseeds, which could rise up prices. The invasion also led to higher prices for fuel and related fertilizers, leading to further food shortages and higher prices. The rise in wheat prices resulting from the conflict has become a problem for the countries, heavily dependent on Russian and Ukrainian wheat exports, and raised fears of social protest. The article analyzes economists’ views on the process of solving the food problems.It should be noted that these main issues will affect further world market prices and inflation will rise. Due to invasion, the US Department of Agriculture published a forecast for the export of grain products from Ukraine. Food and Agriculture Organization of the United Nations published information on the growth of the grain price index. Practical recommendations are provided for solving the problems. The research has been developed to estimate that Ukraine is a leading country in the agricultural sector of the economy, which supplies food to the EU, Africa and India. Due to Russia's invasion into Ukrainian lands, many states may suffer from hunger and if the full-scale intervention into Ukraine is not stopped, then the world will face a food crisis.

У статті проводиться науково обґрунтований аналіз продовольчої проблеми східного регіону України, виходячи з її суттєвого значення для світової проблеми запобігання голоду. Враховуючи той факт, що потенціал зовнішнього виробництва перевищує потреби внутрішнього ринку, необхідно провести дослідження розв'язання продовольчих проблем під час планування розвитку аграрного сектору економіки України. У цій статті розглянуто такі аналітичні питання, які дають змогу оцінити, що Україна протягом багатьох років входить до п'ятірки найбільших експортерів зернових та зернобобових ресурсів. Україна є однією з основних країн, які роблять внесок в аграрний сектор світової економіки. Діяльність майбутніх фахівців при вирішенні продовольчої проблеми залежить від змісту та характеру знань про те, що проблемам сприяли не лише пандемія корона вірусу, а й збройні конфлікти у більшості зазначених країн та зміна клімату, кілька років посухи із сільськогосподарським виробництвом у регіоні. Наведено загальні положення щодо аналізу різних варіантів вирішення даної задачі та оцінено, що аналітичний підхід є найбільш оптимальним, оскільки дозволяє побудувати діаграму порівняння відсоткового змісту найбільш популярних сільськогосподарських культур на посівних площах. Доцільно розглянути процес відбору більшої частини даних, зібраних до вторгнення. Цей дослідницький документ показує той факт, що більша частина занепокоєння пов'язана з нестачею постачання основних сільськогосподарських культур, таких як пшениця, кукурудза та насіння олійних культур, що може призвести до зростання цін. Вторгнення також призвело до підвищення цін на паливо та відповідні добрива, що призвело до подальшого дефіциту продовольства та зростання цін. Зростання цін на пшеницю внаслідок конфлікту стало проблемою для країн, що сильно залежать від російського та українського експорту пшениці, і викликало побоювання соціального протесту. У статті аналізуються погляди економістів на вирішення продовольчої проблеми. Слід зазначити, що ці основні питання надалі впливатимуть на ціни на світовому ринку та зростання інфляції. У зв'язку із вторгненням Міністерство сільського господарства США опублікувало прогноз експорту зернових продуктів із України. Продовольча та сільськогосподарська організація ООН опублікувала дані про зростання індексу цін на зерно. Надано практичні рекомендації щодо вирішення проблем. Дослідження було розроблено для оцінки того, що Україна є провідною країною в аграрному секторі економіки, яка постачає продукти харчування до ЄС, Африки та Індії. Через вторгнення Росії на українські землі багато держав можуть постраждати від голоду і якщо повномасштабну інтервенцію в Україну не зупинити, то на світ чекає продовольча криза.
Продовольча проблема східного регіону України, спричінена війною
Keywords: agriculture; external production; food problems; domestic market; invasion; sowing campaign; sunflower; buckwheat; sugar beet; rye and corn; percentage calculation; salt deposit; сільське господарство; зовнішнє виробництво; продовольчі проблеми; внутрішній ринок; вторгнення; посівна кампанія; соняшник; цукровий буряк; процентний розрахунок; поклади солі